1988
DOI: 10.1002/stem.5530060604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an antimetabolic assay and an antiproliferative assay, both using 3 h‐thymidine incorporation, to test drug sensitivity of human tumors

Abstract: Two assays based on the inhibition of 3H-thymidine incorporation into DNA were used to measure either the antimetabolic or the antiproliferative effects of anticancer drugs. A direct comparison of the two assays was made with cell suspensions obtained from 11 ovarian cancers and 22 malignant melanomas. Drugs with different effects on cell cycle phases were tested by both assays, for a total of 53 drug comparisons. When the sensitivity indices specific for each system was used, a significant association (p less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Also it is possible that further interactive or additive effects among the drugs tested may occur at later times which could not be seen by this assay which measures effects on thymidine incorporation into DNA after three hours incubation with drug. In other studies, we have observed greater effects on DNA synthesis after 24-hour drug incubation, and increased inhibition is also seen in three-day antiproliferative assays [32]. Nevertheless, time-dependent drug effects [36] d o not seem to have led to false negative clinical correlations in the three-hour assay [32].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Also it is possible that further interactive or additive effects among the drugs tested may occur at later times which could not be seen by this assay which measures effects on thymidine incorporation into DNA after three hours incubation with drug. In other studies, we have observed greater effects on DNA synthesis after 24-hour drug incubation, and increased inhibition is also seen in three-day antiproliferative assays [32]. Nevertheless, time-dependent drug effects [36] d o not seem to have led to false negative clinical correlations in the three-hour assay [32].…”
Section: Discussionmentioning
confidence: 51%
“…In other studies, we have observed greater effects on DNA synthesis after 24-hour drug incubation, and increased inhibition is also seen in three-day antiproliferative assays [32]. Nevertheless, time-dependent drug effects [36] d o not seem to have led to false negative clinical correlations in the three-hour assay [32].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation